An updated analysis of 4 randomized ECOG trials of high‐dose interferon in the adjuvant treatment of melanoma. Issue 17 (8th May 2019) - Najjar, Yana G.; Puligandla, Maneka; Lee, Sandra J.; Kirkwood, John M.
Abstract : Background: The pivotal E1684, E1690, E1694, and E2696 trials of adjuvant high‐dose interferon‐α (HDI) enrolled nearly 2000 patients, and established HDI as the standard of care in adjuvant therapy for patients with resected high‐risk melanoma. Herein, the authors present an updated analysis of these 4 trials. Methods: Survival and disease status were updated in September 2016. These data represent a median follow‐up of 17.9 years for the E1684 trial, 12.2 years for the E1690 trial, 16.0 years for the E1694 trial, and 16.5 years for the E2696 trial. Results: The current analysis confirmed the benefit to recurrence‐free survival (RFS) of HDI in the E1684 trial at a median follow‐up of 17.9 years. The RFS benefit in the E1694 trial remained evident at a median follow‐up of 16 years. Furthermore, the results of the current study confirmed the RFS benefit of adjuvant HDI compared with observation in a pooled analysis of the E1684 and E1690 trials. No overall survival benefit was apparent in this pooled analysis. Updated results for the E1690 and E2696 trials did not differ from those previously reported. In addition, to the authors' knowledge, the current study is the first to report a significant difference in melanoma‐specific survival (MSS) between patients treated with HDI compared with the ganglioside GM2/keyhole limpet hemocyanin (GMK) vaccine in the E1694 trial. Conclusions: In patients with resected high‐risk melanoma, adjuvant HDI demonstrated improved RFS in the E1684 and E1694 trials, and improved MSS in a pooled analysis of HDI in the E1694 trial. To the authors' knowledge, these findings represent the most mature level of evidence for the benefit of HDI with respect to RFS and MSS. HDI is the only approved adjuvant treatment for which there are data available in patients with resected stage IIB/IIC melanoma, and remains a reasonable treatment option in this population. Abstract : At 16 years of follow‐up, the E1694 trial, the pivotal trial of high‐dose interferon in patients with resected high‐risk melanoma, is associated with melanoma‐specific survival. The E1684 and E1694 trials are associated with a recurrence‐free survival benefit at a median follow‐up of 17.9 years and 16 years, respectively.